Determination of Kinetic and Thermodynamic Parameters of Pb(II) Ion Adsorption Using Dithizone-Immobilized Coal Fly Ash - Muh Rizal B.; Mudasir Mudasir; Dwi Siswanta; Melvi Muharmi; Vebria Ardina; Teguh Setyawan; Nur Jaya; Defia Indah Permatasari; Revi Maylina Tanjung (Jurnal Kimia Sains dan Aplikasi, 2026)
The immobilization of dithizone on the surface of coal fly ash was successfully achieved, as evidenced by Fourier-transform infrared (FT-IR) and X-ray diffraction (XRD) characterization. The dithizone-immobilized coal fly ash (CFA-Dzt) was then used for Pb(II) ion adsorption. The parameters studied included the effects of pH, kinetics, and thermodynamics on Pb(II) ion adsorption using a batch experimental system. The results showed that the optimum pH for Pb(II) adsorption using CFA-Dzt was 5. The adsorption kinetics of Pb(II) ions followed the pseudo-second-order kinetic model, with an adsorption activation energy of 27.280 kJ mol−1. The Langmuir isotherm model best described the adsorption behavior, with a maximum adsorption capacity of 34.13 mg g−1. Thermodynamic analysis revealed Gibbs free energy changes (ΔG°) of 24.630, 25.850, 26.810, and 28.550 kJ mol−1 at 293, 303, 313, and 323 K, respectively. The enthalpy change (ΔH°) of the adsorption at this temperature range was +12.770 kJ mol−1, indicating that Pb(II) ion adsorption on the adsorbent is an endothermic process, and its entropy change (ΔS°) was +127.290 J mol−1, suggesting that the adsorption of Pb(II) ion on CFA-Dzt is dominantly driven by the entropic factor.